Implementation of Green and Clean Policies in Environmental Governance Perspective in Lamongan Regency - Ahmad Sholikin (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2021)
Lamongan Regency is one of the regions that has issued policies on environmental management, including a 3R-based waste management system (reduce, reuse and recycle) in the form of the Lamongan Green and Clean program and the Waste Bank. This study will analyze the Lamongan Green and Clean policy in an environmental governance perspective. The method used in this research is descriptive qualitative through interview techniques, observation, literature study, and documentation. The theory used in this research is the theory of public policy with the analysis model of the implementation of Van Meter and Van Horn policies. Then, the concepts used in this study are environmental governance and Lamongan Green and Clean. This study aims to describe the implementation of the Lamongan Green and Clean policy whether it has been able to apply the principles of environmental governance. From the results of this study, it is concluded that in implementing the Lamongan Green and Clean program, seen from the perspective of environmental governance, this program has not fully been able to apply the principles of environmental governance.